'Aussie normals': an a priori study to develop clinical chemistry reference intervals in a healthy Australian population. Issue 2 (February 2015) - Koerbin, G.; Cavanaugh, J. A.; Potter, J. M.; Abhayaratna, W. P.; West, N. P.; Glasgow, N.; Hawkins, C.; Armbruster, D.; Oakman, C.; Hickman, P. E.
Abstract : Summary: Development of reference intervals is difficult, time consuming, expensive and beyond the scope of most laboratories. The Aussie Normals study is a direct a priori study to determine reference intervals in healthy Australian adults. All volunteers completed a health and lifestyle questionnaire and exclusion was based on conditions such as pregnancy, diabetes, renal or cardiovascular disease. Up to 91 biochemical analyses were undertaken on a variety of analytical platforms using serum samples collected from 1856 volunteers. We report on our findings for 40 of these analytes and two calculated parameters performed on the Abbott ARCHITECTci8200/ci16200 analysers. Not all samples were analysed for all assays due to volume requirements or assay/instrument availability. Results with elevated interference indices and those deemed unsuitable after clinical evaluation were removed from the database. Reference intervals were partitioned based on the method of Harris and Boyd into three scenarios, combined gender, males and females and age and gender. We have performed a detailed reference interval study on a healthy Australian population considering the effects of sex, age and body mass. These reference intervals may be adapted to other manufacturer's analytical methods using method transference.